The Ɵptimum Decisions in Improving Sustainable Road Network Infrastructure by Using ,GIS , Graph Theory and L-matrix - al-Shuqairy, M. S.; Rajab, Noor A. (Anbar Journal of Engineering Sciences, 2020)
Road network infrastructure is the key indicator of sustainable spatial development, as it affects the economy, environment, and society activities. These can be optimized through minimizing the time the vehicles take on the road, which in turn requires high connectivity and then high accessibility between the nodes of the road network. However, it is necessary to put a development strategy that helps the decision makers to produce relative high accessibility over the development time. In this paper, the vulnerabilities regarding the connectivity and spatial accessibility were pinpointed and analyzed, optimum priorities in sequent new linkages adding are made for developing a sustainable infrastructure with faster enhancement for the spatial accessibility. The results have become a tough guidance for decision makers, and can be adopted as a first step for legislating a strategy for sustainable transportation system